2021
DOI: 10.1161/circoutcomes.120.007411
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care in Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most commonly encountered arrhythmia in clinical practice with an epidemiological coupling appreciated with advancing age, cardiometabolic risk factors, and structural heart disease. This has resulted in a significant public health burden over the years, evident through increasing rates of hospitalization and AF-related clinical encounters. The resultant gap in health care outcomes is largely twinned with suboptimal rates of anticoagulation prescription and adherence, deficits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 126 publications
0
19
0
1
Order By: Relevance
“…Physicians often overestimate bleeding risk, and this apprehension about feeling responsible for a major bleed seems to outweigh their concern about risk of stroke. 14 , 51–53 A study using warfarin identified a previous major bleed as a limiting factor for OAC prescription, although prescription was not influenced by the occurrence of an ischaemic stroke in an untreated AF patient. 54 …”
Section: Adherence and Persistence To Non-vitamin K Antagonist Oral A...mentioning
confidence: 99%
See 4 more Smart Citations
“…Physicians often overestimate bleeding risk, and this apprehension about feeling responsible for a major bleed seems to outweigh their concern about risk of stroke. 14 , 51–53 A study using warfarin identified a previous major bleed as a limiting factor for OAC prescription, although prescription was not influenced by the occurrence of an ischaemic stroke in an untreated AF patient. 54 …”
Section: Adherence and Persistence To Non-vitamin K Antagonist Oral A...mentioning
confidence: 99%
“…Despite the intuitive potential benefit of educational interventions and clinical decision tools, currently there is little robust evidence, 51 , 53 , 76 sometimes even with contradictory findings. 53 , 77 , 78 However, regular scheduled contact with healthcare professionals, patient anticoagulation card recordings, and an active multidisciplinary approach have been proposed to improve patient’s adherence.…”
Section: Strategies To Improve Adherence and Persistence To Non-vitam...mentioning
confidence: 99%
See 3 more Smart Citations